Engagement and Learning Success: Evidence from Three Years of Transformational Teaching Strategies in Online Event Marketing Education - Vergara, Kimberly Christie; Santos, Joseph Emil; Blasa-Cheng, Angelique; Balatbat, Maricel; Vergara, Raymond Allan (Future Science / FSH-PH Publications, 2023)
This study is part of an ongoing teacher-led initiative in understanding the co-creation of a transformative learning experience in the online event marketing classroom. The study measures the impact of student engagement on student-defined learning success in online learning. Using a mixed methods approach, it investigates data collected through a survey questionnaire in three different years from students who enrolled in two course subjects. This study demonstrates that student engagement is significantly correlated with and predicts learner-defined learning success in online learning. Furthermore, it finds that there were statistically significant differences in levels of student engagement and learning success among different cohorts, particularly when compared to cohorts who took the course subject in the later year. The differences may have been a result of the development of skills appropriate for online learning, and in improvements in course content and delivery.